Combination of three species of Zingiberaceae prevents doxorubicin-induced hepatotoxicity - Heny Ekowati; Sarmoko Sarmoko; Retno Widiastuti (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUND Doxorubicin as an anticancer drug has hepatotoxic side effects. Curcuma xanthorrhiza, Curcuma longa and Zingiber officinale are commonly used as herbals in Indonesia and around the world. Several compounds in these plants have antioxidant activities and are known to exhibit protection against doxorubicin-induced toxicities. This study aimed to observe the hepatoprotective effect of a combination of C. xanthorriza, C. longa, and Z. officinale extract on doxorubicin-induced hepatotoxicity in rats. METHODS A total of 28 Wistar male rats were divided into four groups: 1) control group (0.9% NaCl); 2) doxorubicin 5 mg/kg intraperitoneally (ip) four times in 14 days (days 1, 5, 9, 13); 3) doxorubicin + combination of C. xanthorriza, C. longa, and Z. officinale (temulawak, kunyit, and jahe merah, designated as Tekuja) 250 mg/kg/day orally for 14 days; and 4) doxorubicin + Tekuja extract 500 mg/kg/day orally for 14 days. Measurements of parameters based on liver histopathology and the parameters of serum alanine amino transferase (ALT) and aspartate amino tranferase (AST). RESULTS Doxorubicin caused significant elevation in serum ALT and AST enzymes after 14 days of treatment. Rats treated with doxorubicin + Tekuja extract 250 mg/kg/ day showed no histological changes, but had decreased levels of ALT and AST. CONCLUSION This study indicates that the combination of C. xanthorriza, C. longa, and Z. officinale has a protective effect in rats against liver damage induced by doxorubicin